Image processing and communications challenges 9 : 9th International Conference, IP & C 2017 Bydgoszcz, Poland, September 2017 Proceedings /: 9th International Conference, IP & C 2017 Bydgoszcz, Poland, September 2017 Proceedings. ([2018]) - Unknown
No abstract available